The Chromatin Remodeling Factor CHD5 Is a Transcriptional Repressor of WEE1 - Quan, Jinhua (Public Library of Science, 2014)

(untitled)
Loss of the chromatin remodeling ATPase CHD5 has been linked to the progression of neuroblastoma tumors, yet the underlying mechanisms behind the tumor suppressor role of CHD5 are unknown. In this study, we purified the human CHD5 complex and found that CHD5 is a component of the full NuRD transcriptional repressor complex, which also contains methyl-CpG binding proteins and histone deacetylases. The CHD5/NuRD complex appears mutually exclusive with the related CHD4/NuRD complex as overexpression of CHD5 results in loss of the CHD4 protein in cells. Following a search for genes that are regulated by CHD5 in neuroblastoma cells, we found that CHD5 binds to and represses the G2/M checkpoint gene WEE1. Reintroduction of CHD5 into neuroblastoma cells represses WEE1 expression, demonstrating that CHD5 can function as a repressor in cells. A catalytically inactive mutant version of CHD5 is able to associate with a NuRD cofactor but fails to repress transcription. Our study shows that CHD5 is a NuRD-associated transcriptional repressor and identifies WEE1 as one of the CHD5-regulated genes that may link CHD5 to tumor suppression.